Peran Pembiayaan Dalam Meningkatkan Jumlah Mitra UMKM - Asep Soufian; Saiful Anwar; Manager Nasution; Arief Muftie; Riawan Amin; Aries Safari; Jafril Khalil (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
The number of BMT Al Munawwarah partners since 1996 - December 2015 reached 2,803 business units. The large number of BMT Al Munawwarah partners is the cumulative amount of each financing channeled by BMT Al Munawwarah, covering the financing of the musyarokah, mudhorobah, murabaha and ijaroh schemes. It is not known which financing products are more potent in influencing the number of BMT Al Munawwarah partners.To find out the products that potentially influence the number of BMT Al Munawwarah partners, using model model of Multiple Linear Regression (MLR) Linear Logarithm function (Log-lin).The results show that the number of BMT Al Munawwarah partners is significantly influenced by the Ijaroh financing scheme, while for other products, musyarokah, mudhorobah and murabaha does not significantly affect the number of partners. This means that the Ijaroh system is very instrumental to the increasing number of BMT Al Munawwarah partners.